ANALYSIS OF INDONESIA SOCIAL MEDIA USERS’ REACTION ON ENGLISH SPEAKING CONTENT CREATOR - Nabiela A Hidayat; rizqika Amalia; Alya Chairunnisa (Universitas Samudra, 2022)
This article discusses the influence of English-language content creators on Indonesian social media users. The purpose of this study is to find out how influential English content is in improving speaking skills in English. The subjects of this study include several levels of education totaling 63 respondents, the data we use is in the form of a questionnaire using quantitative methods. The results of this study, The author finds that with the existence of special social media (content creators) YouTube is proven to be able to produce a good impact on improving English language skills.